Development of Three-Tier Multiple Choice Diagnostic Test Instruments for Measuring Students’ Misconceptions in Chemical Bonding - Allika Haya Fahrunisa; Ajat Sudrajat (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Development of Three-Tier Multiple Choice Diagnostc Test Instruments for Measuring Students’ Misconceptions in Chemical Bonding. The aim of this study is to determine the need for the development of a three-tier multiple choice diagnostic test instrument in measuring students' misconceptions about chemical bonding material and to know the results of measuring misconceptions using a three- tier multiple choice diagnostic test instrument. This research was conducted at SMAN 1 Rantau Selatan in July 2021 - February 2022. The sample used in this study were students of class X MIA SMAN 1 Rantau Selatan who failed to achieve the KKM value on chemical bonding material. The development in this study used the ADDIE model with two trials. The conclusion of this research are showed that the three tier multiple choice diagnostic test instrument that has been developed meets the characteristics of the substance of the instrument to measure misconceptions in chemical bonding material, the validity of the test was 20 valid question and 20 invalid question. The reliability test showed a realiability lift 0.84. There are 40.3% of students who have misconceptions. For the category of not understanding the concept there are 57.3% of students and the category of understanding the concept there are 2.4% students.  Keywords: three-tier multiple choice, misconception, chemical bond. Abstrak: Pengembangan Instrumen Tes Diagnostik Three Tier Multiple Choice Untuk Mengukur Miskonsepsi Siswa Pada Materi Ikatan Kimia. Penelitian ini bertujuan untuk mengetahui kebutuhan pengembangan instrumen tes diagnostik pilihan ganda tiga tingkat dalam mengukur miskonsepsi siswa pada materi ikatan kimia dan untuk mengetahui hasil pengukuran miskonsepsi menggunakan instrumen tes diagnostik pilihan ganda tiga tingkat. Penelitian ini dilaksanakan di SMAN 1 Rantau Selatan pada bulan Juli 2021 – Februari 2022. Sampel yang digunakan dalam penelitian ini adalah siswa kelas X MIA SMAN 1 Rantau Selatan yang tidak mencapai nilai KKM pada materi ikatan kimia. Pengembangan dalam penelitian ini menggunakan model ADDIE dengan dua kali uji coba. Kesimpulan dari penelitian adalah instrumen tes diagnostik pilihan ganda tiga tingkat yang telah dikembangkan memenuhi karakteristik substansi instrumen untuk mengukur miskonsepsi pada materi ikatan kimia, validitas tes menunjukkan hasil bahwa terdapat 20 pertanyaan valid dan 20 pertanyaan tidak valid. . Uji reliabilitas menunjukkan hasil reliabilitas sebesar 0,84. Hasil pengukuran adalah terdapat 40,3% siswa yang mengalami miskonsepsi. Untuk kategori tidak  paham konsep terdapat 57,3% siswa dan kategori paham konsep ada 2,4% siswa. Kata kunci: pilihan ganda tiga tingkat, miskonsepsi, ikatan kimia.DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.12